Characterization of Kowoe snail and its antioxidant activity - Haslianti Haslianti; Mita Gabriella Inthe; Ermayanti Ishak (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Gold snail is called “Kowoe” in Celebes Island. They are widely utilized by people as food. This snail also has many properties and benefits. The aims of this study were to determine the best solvent to extract the bioactive components of snails and measure the antioxidant activity. The proximate analysis was caried out, then quantitative test of antioxidant activity by DPPH method was measured. The results of morphometric measurements showed the meat yield 11.86%. The proximate analysis of fresh meat consisted of water content 65.79%, 18.14% protein, 10.49% ash, 4.14% carbohydrates, and fats 3.44%, while the moisture content of dried meat contained 40/ 04%, 38.06% protein, carbohydrates 10.66%, ash 8.53% and 2.70% fat, respectively. The yield of extraction of the active compound using chloroform (non-polar) was 1.78%, ethyl acetate (semi-polar) was 3.41% and 6.63% methanol (polar). The snails kowoe contain more the polar of active compounds. The antioxidant activity of crude extract in methanol solvent (polar) had IC50 values 111.28 ppm (moderate).